2007
DOI: 10.1210/en.2007-1132
|View full text |Cite
|
Sign up to set email alerts
|

Collective and Individual Functions of Leptin Receptor Modulated Neurons Controlling Metabolism and Ingestion

Abstract: Two known types of leptin-responsive neurons reside within the arcuate nucleus: the agouti gene-related peptide (AgRP)/neuropeptide Y (NPY) neuron and the proopiomelanocortin (POMC) neuron. By deleting the leptin receptor gene (Lepr) specifically in AgRP/NPY and/or POMC neurons of mice, we examined the several and combined contributions of these neurons to leptin action. Body weight and adiposity were increased by Lepr deletion from AgRP and POMC neurons individually, and simultaneous deletion in both neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
250
0
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 296 publications
(279 citation statements)
references
References 37 publications
20
250
0
9
Order By: Relevance
“…We have previously shown that SOCS3 expression is Cre-dependent, and its expression is upregulated approximately twofold in Cre-expressing cells upon recombination (6). The Tg.Agrp-Cre mice have been used and validated in a number of independent studies (7,(25)(26)(27)(28)(29)(30)(31). The resultant mutant mice, termed AgRP-SOCS3-OE, were born in Mendelian ratio with no detectable gross abnormalities.…”
Section: Expression Of Socs3 In Agrp Neurons Is Dynamically Modulated Inmentioning
confidence: 99%
“…We have previously shown that SOCS3 expression is Cre-dependent, and its expression is upregulated approximately twofold in Cre-expressing cells upon recombination (6). The Tg.Agrp-Cre mice have been used and validated in a number of independent studies (7,(25)(26)(27)(28)(29)(30)(31). The resultant mutant mice, termed AgRP-SOCS3-OE, were born in Mendelian ratio with no detectable gross abnormalities.…”
Section: Expression Of Socs3 In Agrp Neurons Is Dynamically Modulated Inmentioning
confidence: 99%
“…Instead, we speculate that excess delivery of lipoproteins secondary to enhanced accumulation of plasma lipoproteins might contribute to hepatic triglyceride accumulation in LEPR-defi cient mice. Another possibility is that these mice have reduced oxidation of triglycerides due to decreased leptin signaling ( 45 ).…”
Section: Leptin Receptor Defi Ciency Affects Plasma and Tissue Lipid mentioning
confidence: 99%
“…First db/db mice have reduced lipoprotein lipase activity ( 52 ), thereby reducing lipoprotein catabolism, while promoting hyperlipidemia. Second, total lipid oxidation is reduced in db/db mice and other cell-specifi c LEPR defi ciencies, causing an accumulation of fat ( 45 ). Overall decreases in lipid utilization would promote lipid accumulations in serum and tissue.…”
Section: Leptin Receptor Defi Ciency Affects Plasma and Tissue Lipid mentioning
confidence: 99%
“…Deletion of leptin receptors on AgRP neurons increases body weight and adiposity [276]. When leptin receptors were deleted from both POMC and AgRP neurons, the mice became more obese, leading the authors to conclude that POMC and AgRP neurons work synergistically in response to leptin [276]. Insulin also acts on AgRP neurons in the arcuate nucleus [141,189].…”
Section: Agrp/npy Neuronsmentioning
confidence: 99%